Are intervertebral disc tissue cells damaged when attempting to prevent thrombus formation using dabigatran, a new oral anticoagulant? - Kaplan, Necati; Karaaslan, Numan; Yılmaz, İbrahim; Yaşar Şirin, Duygu; Akgün, Feride Sinem; Çalışkan, Tezcan; Şimşek, Abdullah Talha; Özbek, Hanefi (Turkish Neurosurgical Society, 2019)
AIM: To investigate the effect of dabigatran, a new oral anticoagulant, on human primary cell cultures isolated from intact intervertebral disc tissue. MATERIAL and METHODS: Cell cultures were prepared from tissues obtained from six cases who had undergone surgery due to spinal trauma. Dabigatran, an active pharmacological agent, was applied to intact annulus fibrosus (AF)/nucleus pulposus (NP) primary cell cultures from the study group. After performing cell viability, toxicity, and proliferation tests on all cultures in the control and study groups, the surface morphologies of the samples were evaluated. Subsequently, chondroadherin (CHAD), cartilage oligomeric matrix protein (COMP), and matrix metalloproteinase (MMP)-13 and -19 expressions were measured via a real-time polymerase chain reaction (RT-PCR). Data were analyzed statistically. RESULTS: In the proliferation assays performed on the 20th day of the study, cells in the dabigatran-supplemented group were reported to have lost 46.37% more viability than those in the control group. Expressions of all genes examined except MMP-13 were evaluated in the control group by time, but in contrast to the control group results, COMP and MMP-19 gene expressions decreased in the dabigatran-treated group. No CHAD or MMP-13 expression was noted in these cultures. CONCLUSION: The potential for a systemically applied drug to accumulate in tissue and negatively affect surrounding tissues and microstructures must be emphasized.
Keywords: Cytotoxicity; Dabigatran; Deep Vein Thrombosis; Intervertebral Disc Cells; Primary Cell Cultures